FLEXIBLE ENTREPRENEURIAL ACTIVITY AND EFFECTIVE SOCIAL POLICY - Ganiev Muhammadjon Khalilovich (Journal of Artificial Intelligence and Digital Economy, 2024)
Objective: This study aims to explore the role of entrepreneurship, specifically social entrepreneurship, in fostering economic and social development, particularly in Uzbekistan. It examines the dual impact of entrepreneurship on economic growth and social welfare, focusing on job creation, poverty reduction, and innovation. Methods: The research distinguishes between two primary models of entrepreneurship: traditional and innovative. Traditional entrepreneurship is characterized by resource efficiency and conventional management methods, while innovative entrepreneurship emphasizes creativity, technological adoption, and new solutions. Data from Uzbekistan's small business sector, government initiatives, and social entrepreneurship laws were analyzed to assess their impact on economic and social outcomes. Results: The study found that entrepreneurship, especially in small businesses, has significantly contributed to Uzbekistan's economic growth, creating jobs and fostering competition. Despite challenges, such as the COVID-19 pandemic, the government’s support for micro-businesses has led to increased entrepreneurial activity. Social entrepreneurship, particularly in vulnerable sectors, is gaining prominence, with legal frameworks supporting its growth. Novelty: This research highlights the emerging significance of social entrepreneurship in Uzbekistan, offering a fresh perspective on its potential to address social issues. It introduces the concept of a legal framework for social enterprises, which reinvest profits into social causes, marking a new phase in the country’s socio-economic development.